Neurogenin3 is differentially required for endocrine cell fate specification in the intestinal and gastric epithelium - Jenny, Marjorie (Oxford University Press, 2002)
Endocrine cells of the pancreas and the gastrointestinal tract derive from multipotent endodermal stem cells. We have shown previously that the basic helix– loop–helix (bHLH) transcription factor neurogenin3 (ngn3) is required for the specification of the endocrine lineage in uncommitted progenitors in the developing pancreas. We investigate herein the expression and the function of ngn3 in the control of endocrine cell development in the intestinal and gastric epithelium. Our results indicate that as in the pancreas, gastrointestinal endocrine cells derive from ngn3-expressing progenitors. Mice homozygous for a null mutation in ngn3 fail to generate any intestinal endocrine cells, and endocrine progenitor cells are lacking. The other main intestinal epithelial cell types differentiate properly. In contrast, in the glandular stomach, the differentiation of the gastrin- (G cells) and somatostatin (D cells)-secreting cells is impaired whereas serotonin- (enterochromaffin EC cells), histamine- (enterochromaffin-like ECL cells) and ghrelin (X/A cells)-expressing cells are still present. Thus, ngn3 is strictly required for endocrine cell fate specification in multipotent intestinal progenitor cells, whereas gastric endocrine development is both ngn3 dependent and independent.